2018
DOI: 10.1113/jp276626
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of cortical GABA in human motor learning

Abstract: Key points The ability to learn new motor skills is supported by plasticity in the structural and functional organisation of the primary motor cortex in the human brain.Changes inhibitory to signalling by GABA are thought to be crucial in inducing motor cortex plasticity.This study used magnetic resonance spectroscopy (MRS) to quantify the concentration of GABA in human motor cortex during a period of motor learning, as well as during a period of movement and a period at rest.We report evidence for a reduction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
131
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(155 citation statements)
references
References 40 publications
17
131
5
2
Order By: Relevance
“…These results suggest that, under the effect of excitatory stimulation, motor sequence learning, in comparison to random motor execution, resulted in a decrease in DLPFC inhibitory tone. Interestingly, these results are in line with evidence of learning-induced decreases in M1 GABA levels during (Kolasinski et al, 2018), immediately after (Floyer-Lea et al, 2006) but also after 6 weeks of motor sequence learning (Sampaio-Baptista et al, 2015). Importantly and consistent with our results, these M1 GABA changes have been described to be learning-specific, as no such effects were observed after random task practice (Floyer-Lea et al, 2006;Kolasinski et al, 2018).…”
Section: Dlpfc Stimulation Altered the Relationship Between Dlpfc Gabsupporting
confidence: 92%
See 3 more Smart Citations
“…These results suggest that, under the effect of excitatory stimulation, motor sequence learning, in comparison to random motor execution, resulted in a decrease in DLPFC inhibitory tone. Interestingly, these results are in line with evidence of learning-induced decreases in M1 GABA levels during (Kolasinski et al, 2018), immediately after (Floyer-Lea et al, 2006) but also after 6 weeks of motor sequence learning (Sampaio-Baptista et al, 2015). Importantly and consistent with our results, these M1 GABA changes have been described to be learning-specific, as no such effects were observed after random task practice (Floyer-Lea et al, 2006;Kolasinski et al, 2018).…”
Section: Dlpfc Stimulation Altered the Relationship Between Dlpfc Gabsupporting
confidence: 92%
“…Importantly and consistent with our results, these M1 GABA changes have been described to be learning-specific, as no such effects were observed after random task practice (Floyer-Lea et al, 2006;Kolasinski et al, 2018). We argue that, similar to M1, the decrease in DLPFC GABA+ levels might reflect disinhibition processes that promote successful learning (Kolasinski et al, 2018;Stagg et al, 2011).…”
Section: Dlpfc Stimulation Altered the Relationship Between Dlpfc Gabsupporting
confidence: 90%
See 2 more Smart Citations
“…Pharmacological studies have suggested that SICI is mediated by type A gamma‐aminobutyric acid (GABA A ) receptors (Di Lazzaro et al, ). Studies of the human motor cortex using TMS have reported increased cortical excitability and decreased SICI after motor learning (Leung, Rantalainen, Teo, & Kidgell, ; Rosenkranz, Kacar, & Rothwell, ), suggesting that GABA A plays an important role in human motor learning (Kolasinski & Hinson, ).…”
Section: Introductionmentioning
confidence: 99%